PENGARUH KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR IPA SISWA - José Pinto Casquilho; Feliza Sinaga; Neni Septiani; Sri Wina Oktavia; Nikma Nur Qoidah; Endah Febri Setiya Rini (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to determine the effect of critical thinking skills on student learning outcomes. Researchers conducted research using quantitative methods and associative approaches. The instruments used were questionnaires and question sheets given to students to see student responses to the variables used. The research sample is 22 State Junior High School 1 Muaro Jambi class IX students. The results obtained prove that there is an influence of critical thinking skills on student learning outcomes at State Junior High School 1 Muaro Jambi. The update from the current research is in the method used, which shows more precise results based on the data obtained from the sample. The limitations of this study are the small number of research samples and less varied results. So, recommendations for further research to be able to add research samples and the results obtained are better.